Pendampingan Local Role Model pada Ibu Bayi terhadap Kelengkapan Status Imunisasi DPT-HB - Ivana Devitasari (Jurnal Surya Medika (JSM), 2022)
Information about immunizations delivered by health workers to the baby's mother is not optimal because of rejection from the community. Hence, it impacts the coverage of immunization visits which is low, and increases the incidence of morbidity and mortality in infants. Therefore, through community empowerment, namely the use of local role models, the hope will be to impact the community to be aware and willing to bring their children to the immunization service post. To determine the effect of using a local role model on the completeness of the primary immunization visit status of DPT-HB in mothers of infants aged 2-3 months. Randomized controlled trial design in four Palangka Raya City Health Centers in December 2018 - February 2019 in 80 districts divided into two groups (40 pairs of mothers and babies use local role models, and 40 pairs of mothers and infants use immunization officers) with inclusion criteria for mothers of infants aged 2-3 months or more who live in the study area and have not been immunized against DPT-HB. A local role model is a mother who has experience completing three series of DPT-HB immunizations for her baby. Data analysis in this study used univariable, bivariable, and multivariable. Statistical tests showed that the use of local role models had an effect (p = 0.012) of 70% on the completeness of the primary immunization visit status of DPT-HB, Another factor that influences the entirety of DPT-HB primary immunization visit status is access to information sources (p = 0.022). The use of local role models proved to have a significant effect on the completeness of the primary immunization visit status of DPT-HB.